Strategies in Solving Stoichiometric Algorithmic Problems among High School Students: A Grounded Theory Approach - Erna Widhi Astuti; I Wayan Dasna; Munzil (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2026)
This study aims to identify students’ strategies in solving algorithmic stoichiometry problems using a qualitative Grounded Theory approach. A total of 25 twelfth-grade students were given algorithmic stoichiometry problems involving concepts such as mole, molar mass, limiting reactant, and mass–mole–volume relationships. Based on the analysis of students’ written responses, 15 students representing various problem-solving strategies were selected for in-depth semi-structured interviews to explore their thinking patterns and the difficulties they encountered. The data analysis was conducted through open coding, axial coding, selective coding, and the constant comparative method until theoretical saturation was reached. Based on the analysis of written responses and in-depth interviews, a theory concerning students’ levels of understanding and strategies for solving algorithmic stoichiometry problems was generated. This theory explains three main aspects: students’ understanding of stoichiometry, which develops through several levels; problem-solving strategies that are influenced by the depth of understanding at each level; and common inhibiting factors, such as students’ lack of comprehensive understanding of fundamental stoichiometric concepts.